The anatomy of exhumed river‐channel belts: Bedform to belt‐scale river kinematics of the Ruby Ranch Member, Cretaceous Cedar Mountain Formation, Utah, USA. Issue 7 (17th July 2020) - Cardenas, Benjamin T.; Mohrig, David; Goudge, Timothy A.; Hughes, Cory M.; Levy, Joseph S.; Swanson, Travis; Mason, Jasmine; Zhao, Feifei
Abstract: Many published interpretations of ancient fluvial systems have relied on observations of extensive outcrops of thick successions. This paper, in contrast, demonstrates that a regional understanding of palaeoriver kinematics, depositional setting and sedimentation rates can be interpreted from local sedimentological measurements of bedform and barform strata. Dune and bar strata, channel planform geometry and bed topography are measured within exhumed fluvial strata exposed as ridges in the Ruby Ranch Member of the Cretaceous Cedar Mountain Formation, Utah, USA. The ridges are composed of lithified stacked channel belts, representing at least five or six re‐occupations of a single‐strand channel. Lateral sections reveal well‐preserved barforms constructed of subaqueous dune cross‐sets. The topography of palaeobarforms is preserved along the top surface of the outcrops. Comparisons of the channel‐belt centreline to local palaeotransport directions indicate that channel planform geometry was preserved through the re‐occupations, rather than being obscured by lateral migration. Rapid avulsions preserved the state of the active channel bed and its individual bars at the time of abandonment. Inferred minimum sedimentation durations for the preserved elements, inferred from cross‐set thickness distributions and assumed bedform migration rates, vary within a belt from one to ten days. Using only these local sedimentological measurements, the depositional setting is interpreted as a fluvial megafan, given the similarity in river kinematics. This paper provides a systematic methodology for the future synthesis of vertical and planview data, including the drone‐equipped 2020 Mars Rover mission, to exhumed fluvial and deltaic strata.